Evaluation of cut-off values of interferon-gamma-based assays in the diagnosis of M-tuberculosis infection - (:unkn) unknown (INT UNION AGAINST TUBERCULOSIS LUNG DISEASE (I U A T L D), 2008)
SETTING: A chest disease centre in Istanbul, Turkey. OBJECTIVE: The diagnostic accuracy of interferon-gamma-based assays for Mycobacterium tuberculosis infection may be improved by using lower cut-off values for the tuberculin skin testing (TST), QuantiFERON-TB Gold (QFT) and T-SPOT.TB (T-SPOT) assays. DESIGN: Three assays, TST, QFT and T-SPOT, were evaluated for their diagnostic performance with respect to different cut-off values. This evaluation was carried out in a comparative study involving 100 patients with untreated culture-confirmed cavitary pulmonary tuberculosis (TB) and 47 healthy subjects. RESULTS: The sensitivities of the assays were: TST 70%, QFT 78% and T-SPOT 83.5%, while their specificities were TST 35%, QFT 89.4% and T-SPOT 84.8%. Both QFT and T-SPOT were significantly more specific than TST (both P < 0.001), but were similiar to each other (P = 0.5). Receiver operating characteristic analysis revealed that a cut-off value of 0.818 IU/ml for QFT maximises specificity without significant loss of test sensitivity. Using lower cut-off values for T-SPOT and TST, however, also increased the sensitivity of the assay but resulted in a significant decrease in specificity. CONCLUSION: Lower cut-off values for TST, QFT and T-SPOT increased the sensitivity of each assay, but only with a lower cut-off value for QFT could specificity be maintained.
Keywords: pulmonary tuberculosis; QuantiFERON-TB Gold; T-SPOT.TB; sensitivity; specificity; SKIN-TEST; ESAT-6; INDIVIDUALS; ENUMERATION; PREVALENCE; VACCINES; BURDEN; BOVIS; BCG